Inteligencia emocional en la enseñanza remota en docentes de educación inicial de instituciones educativas públicas de la ciudad de Nauta 2021 - Chamoli Cahuaza de Reategui, Carlina (2022)
This research has been developed with the aim of arguing whether there is a good level of emotional intelligence in remote teaching in initial education teachers who work in public educational institutions in the city of Nauta, 2021. The research is basic, with a descriptive design with a single variable and cross-sectional. The population considered was 120 initial level teachers, the sample was 40 teachers for convenience. The technique, which will be used in data collection, will be the interview and the instrument will be the BarOn Inventory questionnaire (I-CE) abbreviated, the instruments were previously validated by expert judgment. The conclusion is that there is a good level of emotional intelligence in remote teaching in initial education teachers who work in public educational institutions in the city of Nauta, 2021. In this ratio, we have a calculated general mean of 6.106 and a standard deviation of 9.30, which indicates that there is a significant difference in the values of the components of emotional intelligence.